Effectiveness of Interactive Media in Enhancing Students Science Concept Understanding - Yunita, Yunita; Irawan, Turino Adi (Riwayat: Educational Journal of History and Humanities, 2025)
Science learning is essential for developing students critical thinking and conceptual understanding; however, conventional lecture-based approaches often fail to address abstract scientific concepts. The advancement of educational technology offers opportunities through interactive media, which provides engaging and participatory experiences that can transform abstract phenomena into more concrete and accessible forms. This study aims to analyze the effectiveness of interactive media in enhancing students understanding of science concepts. A qualitative literature study design was employed, focusing on peer-reviewed publications between 2015 and 2023 obtained from international and national databases. Content analysis was applied to synthesize findings across studies. The results indicate that interactive media significantly improves students conceptual understanding by enabling them to visualize abstract processes such as molecular structures, energy transformations, and ecological interactions. It also enhances motivation and engagement, as students find learning activities more enjoyable, meaningful, and interactive. Moreover, interactive tools support differentiated learning, accommodating diverse student abilities and learning styles, thus promoting inclusive education. Evidence from both international and Indonesian contexts demonstrates that interactive media is effective even in resource-constrained settings when appropriately designed. Overall, this study concludes that integrating interactive media into science classrooms is not only a technological enhancement but also a pedagogical necessity. While most existing research highlights cognitive outcomes, further exploration of affective and psychomotor impacts is required. The findings reinforce the potential of interactive media to align with 21st-century education goals, particularly the Merdeka Curriculum, which emphasizes project-based, student-centered, and experiential learning.